The role of probiotics in supporting celiac disease management - a review of current research and therapeutic perspectives - Aleksandra Cieplak; Zuzanna Czyżewicz; Aleksandra Kołodziej; Nadia Hornig; Wiktoria Zamirska (Journal of Education, Health and Sport)
Introduction and purpose: Celiac disease is a chronic autoimmune disorder that damages the small intestinal mucosa in response to the ingestion of gluten. Although a gluten-free diet is the only effective treatment, many patients experience incomplete resolution of symptoms, highlighting the need to explore new therapeutic strategies. This review aims to evaluate the available clinical evidence on the effect of probiotics on celiac disease symptoms and to analyze their potential therapeutic benefits.